2018
DOI: 10.2478/enr-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

A short review of primary aldosteronism in a question and answer fashion

Abstract: Primary aldosteronism is the most common and a treatable case of secondary hypertension. Only patients with unilateral adrenal diseases are eligible for surgery, while patients with bilateral and non-surgically correctable PA are usually treated by mineralocorticoid receptor antagonist (MRA). Thus, the distinction between unilateral and bilateral aldosterone hypersecretion is crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…This condition is also called familial hyperaldosteronism type 1. In very young patients with PA, testing for germline mutations in KCNJ5 is recommended to diagnose familial hyperaldosteronism type 3 ( 41 ).…”
Section: Laboratory Investigation Of Hypokalemiamentioning
confidence: 99%
“…This condition is also called familial hyperaldosteronism type 1. In very young patients with PA, testing for germline mutations in KCNJ5 is recommended to diagnose familial hyperaldosteronism type 3 ( 41 ).…”
Section: Laboratory Investigation Of Hypokalemiamentioning
confidence: 99%
“…Therefore, serum potassium performed best if the cut-off to detect primary aldosteronism was set at <3.9 mmol/L which is above routine usage and guideline recommendations [ 16 , 17 ]. This may also be the cause to assume that the majority of patients affected by PA are normokalemic [ 18 , 19 , 20 ]. However, we could show that serum potassium along with SUSPPUP and renin normalizes during pharmacologic treatment and—even more and along with the ARR—after surgery, indicating that salt preservation on the expense of potassium is reversed with anti-mineralocorticoid treatment or removal of aldosterone-producing adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…PA is the most common and curable cause of secondary hypertension [1]. PA was initially described by Lity ński in Poland in 1953, then 2 years later in 1955 by Conn in the USA [2]. PA is associated with excessive and autonomous production of aldosterone.…”
Section: Introductionmentioning
confidence: 99%
“…Hypokalaemia had originally been considered a principal feature of PA; however, recent studies have reported that hypokalaemia is present only in 28% of PA patients. The most common causes of PA are bilateral idiopathic hypertrophy (BIH) (60% of cases) and aldosterone-producing adenomas (APAs; called Conn's Syndrome) (35% of cases, although these percentages are changing over time) [2]. The rare causes of PA are unilateral hyperplasia, familial hyperaldosteronism (types I-IV), aldosterone-producing carcinoma, and ectopic aldosterone production [1].…”
Section: Introductionmentioning
confidence: 99%